Modelling the Effects of Non-Steady State Transport Dynamics on the Sulfur and Oxygen Isotope Composition of Sulfate in Sedimentary Pore Fluids - Fotherby, Angus; Bradbury, Harold J.; Antler, Gilad; Sun, Xiaole; Druhan, Jennifer L.; Turchyn, Alexandra V. (Frontiers in Earth Science, 2021)
We present the results of an isotope-enabled reactive transport model of a sediment column undergoing active microbial sulfate reduction to explore the response of the sulfur and oxygen isotopic composition of sulfate under perturbations to steady state. In particular, we test how perturbations to steady state influence the cross plot of the sulfur versus oxygen isotopic composition of sulfate. The slope of the apparent linear phase (SALP) in the cross plot of the sulfur versus oxygen isotopic composition of sulfate has been used to infer the mechanism, or metabolic rate, of microbial metabolism, making it important that we understand how transient changes might influence this slope. Tested perturbations include changes in boundary conditions and changes in the rate of microbial sulfate reduction in the sediment. Our results suggest that perturbations to steady state influence the pore fluid concentration of sulfate and its sulfur and oxygen isotopic composition but have a minimal effect on SALP. Furthermore, we demonstrate that a constant advective flux in the sediment column has no measurable effect on SALP. We conclude that changes in the SALP after a perturbation are not analytically resolvable after the first 5% of the total equilibration time. This suggests that in sedimentary environments the SALP can be interpreted in terms of microbial metabolism and not in terms of environmental parameters.